Valuing Crop Biodiversity: On-Farm Genetic Resources and Economic Change 2005
DOI: 10.1079/9780851990835.0177
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of cereal diversity in villages of northern Ethiopia.

Abstract: This chapter compares factors explaining the inter- (interspecific) and intracrop (infraspecific diversity) of cereals grown by villages in Peasant Associations (PAs) of the northern Ethiopian highlands of Amhara and Tigray, building on the household-level analysis presented for the same sites in Chapter 6 [Explaining the diversity of cereal crops and varieties grown on household farms in the highlands of northern Ethiopia by S. Benin, M. Smale and J. Pender, pp. 78-96]. The village is the smallest social unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…This is consistent with evidence that the eastern part of the region has the worst conditions for agricultural production (Gebremedhin, Smale, and Pender 2006). The use of improved seeds does not have a statistically significant effect.…”
Section: Econometric Resultssupporting
confidence: 79%
“…This is consistent with evidence that the eastern part of the region has the worst conditions for agricultural production (Gebremedhin, Smale, and Pender 2006). The use of improved seeds does not have a statistically significant effect.…”
Section: Econometric Resultssupporting
confidence: 79%
“…Makhura (2001), Dossa et al (2008), Millar and Photakoun (2008), Mertz et al (2009), Ampaire and Rothschild (2010) and Namonje-Kapembwa et al (2016), in their studies, have mentioned sales channels where animal producers feel it is relatively easier to access, participate, negotiate and sell. Gebremedhin et al (2004) suggest that TCs limit accessing a sales channel. Several authors have commonly found that ICs related to difficulty in finding information and time spent researching price information, and NCs expressed in time spent in negotiation process, low bargaining power, and transport cost, depending on the distance from markets negatively influence the producer's choice to sell at formal market (Hobbs, 1996b;Hobbs, 1997;Key et al., 2000;Hudson and Lusk, 2004;Ruijs et al, 2004;Gong et al, 2007;Kyeyamwa et al, 2008;Broderick et al, 2011;Woldie and Nuppenau, 2011;Lijia and Xuexi, 2012;Jordaan and Grove, 2013).…”
Section: Sales Channel Conveniencementioning
confidence: 99%
“…For example, in the case of cereal production in Ethiopia, Gebremedhin et al . (2004) conclude that the effect of transaction costs on diversity is rather specific to the type of location and crop that is being considered. In Bolivia, Vadez et al .…”
Section: Pre-harvest Decision Making: Conceptual Frameworkmentioning
confidence: 99%
“…The significance of transaction costs in agriculture depends on their influence on agricultural decision making at different stages of the agricultural cycle, including whether the costs are associated with input-market-to-farm, on-farm or farm-to-final-market transaction costs. A number of studies have sought to test the hypothesis that transactions costs, which limit market access, influence specialization and, therefore, the level of genetic material used on farms (Aguirre et al ., 1998; Gebremedhin et al ., 2004; Vadez et al ., 2004; Wale and Mburu, 2004). However, there are a number of limitations to these studies.…”
Section: Seed Markets Transaction Costs and Agriculturementioning
confidence: 99%